2010
DOI: 10.1177/0017896910364570
|View full text |Cite
|
Sign up to set email alerts
|

Health beliefs about osteoporosis and osteoporosis screening in older women and men

Abstract: Objective To examine older adults' beliefs about osteoporosis and osteoporosis screening to identify barriers to screening. Design Cross-sectional mailed survey. Setting Western Pennsylvania. Methods Surveys were mailed to 1830 women and men aged 60 years and older. The survey assessed sociodemographic characteristics, osteoporosis and general health-related characteristics, and beliefs about osteoporosis severity, susceptibility, screening self-efficacy, and screening response efficacy. Analyses include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
21
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 38 publications
6
21
3
Order By: Relevance
“…These results reinforce others' findings of a generally low perceived susceptibility to OP among older men (18, 26) and underscore the importance of incorporating patient constructions of risk into programs to improve risk reduction behaviors (15, 26,27). It also echoes the findings of Gaines et al about men's limited knowledge of OP risk factors and prevention behaviors in a largely middle class Caucasian sample (15).…”
Section: Discussionsupporting
confidence: 85%
“…These results reinforce others' findings of a generally low perceived susceptibility to OP among older men (18, 26) and underscore the importance of incorporating patient constructions of risk into programs to improve risk reduction behaviors (15, 26,27). It also echoes the findings of Gaines et al about men's limited knowledge of OP risk factors and prevention behaviors in a largely middle class Caucasian sample (15).…”
Section: Discussionsupporting
confidence: 85%
“…(73) In a survey of older adults, increased weight was associated with both level of belief in susceptibility to osteoporosis and efficacy of screening. (74) Although screening acceptance for osteoporosis has not been as well-studied as for cancer screening, for instance, it is likely that weight presents a similar patient barrier for DXA screening as for mammography. (75) Comorbidities that are more frequent in obese people may also play a role in a lower frequency of screening.…”
Section: Bone Density Testing In Overweight and Obese Individualsmentioning
confidence: 99%
“…Johnson et al (2008) found that men aged 18 -25 had significantly lower perceived susceptibility to osteoporosis than women in the 30 -50 and over 50 age groups. Regarding older men, Nayak et al (2010) found with osteoporosis screening in older women and men over 60 that men did not believe as strongly in their perceived susceptibility to osteoporosis as women. Doheny et al (2007) found that in men and women over 50 with DEXA scans, women had high perceived susceptibility to and severity of osteoporosis, men had low perceived susceptibility to and severity to osteoporosis, and men felt more confident of their ability to engage in weightbearing physical activity.…”
Section: Osteoporosis Health Beliefs In Menmentioning
confidence: 94%
“…Swaim, Barner, and Brown (2008) found that postmenopausal women were neutral on perceived susceptibility to and severity of osteoporosis. Nayak et al (2010) found regarding osteoporosis screening in older women (and men over 60) that individuals had low perceived susceptibility to osteoporosis but a high perceived severity of osteoporosis. Older individuals believed less strongly than younger individuals in osteoporosis severity, and women believed more strongly than men in osteoporosis susceptibility.…”
mentioning
confidence: 99%